10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Objective To assess the efficacy and safety of fenfluramine in patients with Dravet syndrome (DS) stratified by age, number of previously attempted antiseizure medications (ASMs), and SCN1A pathogenic variant status. Methods In this post hoc analysis, data from three randomized controlled trials (RCTs) in patients with DS (2-18 years) were pooled and stratified by age (<4; ≥4 years), number of previous ASMs (1-3; 4-6; ≥7), and SCN1A pathogenic variant status (SCN1A+; SCN1A-). Stratified groups were assessed and compared with the pooled placebo group (change in monthly convulsive seizure frequency [MCSF], longest convulsive seizure-free interval, and Clinical Global Impression-Improvement [CGI-I] scale scores rated by parents/caregivers and investigators), and safety (treatment-emergent adverse events [TEAEs]: frequency, days to onset, and proportion resolved). Results Among 348 patients included in the RCTs, 216 were randomized to fenfluramine (0.7 mg/kg/day, n = 88; 0.4 mg/kg/day [with stiripentol], n = 43; 0.2 mg/kg/day, n = 85) and 132 to placebo. Compared with placebo, fenfluramine treatment (all doses combined) resulted in greater MCSF reductions, greater increases in longest convulsive seizure-free intervals, and a higher proportion of parents/caregivers and investigators reporting clinically meaningful improvement ("Much Improved", "Very Much Improved") on CGI-I scores across all stratified groups. CGI-I scores were consistent across fenfluramine doses in most stratified groups, but patients with the fewest number of previous ASMs had the greatest frequency of clinically meaningful improvement on investigator-rated CGI-I scores. Safety outcomes were similar across all strata. Most TEAEs resolved by end-of-study. Significance Fenfluramine treatment was associated with improved seizure outcomes and global functioning compared with placebo regardless of age, number of previous ASMs, and SCN1A status in patients with DS. Fenfluramine was well-tolerated; no new safety signals were identified. Further studies with larger sample sizes (including adults) and a priori inferential analyses of stratified groups are warranted. Plain language summary Patients with Dravet syndrome struggle with seizures and everyday life. In three studies, patients aged 2-18 years received fenfluramine or placebo (sugar pill). Fenfluramine lowered seizures without many side effects. Researchers combined results from these studies to see how fenfluramine worked in different patient groups based on age, number of previous medications, and a gene called SCN1A. They looked at seizure reduction and whether doctors felt patients had improved. In all groups, fenfluramine worked better than placebo, with similar side effects. Researchers believe fenfluramine helped these patients, but some groups were small, so these results need to be confirmed.